PENGARUH E-SERVICE QUALITY APLIKASI JAMSOSTEK MOBILE (JMO) TERHADAP KEPUASAN PENERIMA MANFAAT JAMINAN HARI TUA (JHT) PADA BPJS KETENAGAKERJAAN KANTOR CABANG BUKITTINGGI - Almelia Susanti; Nora Eka Putri (STKIP Subang, 2026)
The digital transformation of public services has encouraged BPJS Ketenagakerjaan to develop the Jamsostek Mobile (JMO) application to facilitate access to Old Age Security (JHT) services. However, various user complaints regarding system errors, login difficulties, and other technical issues indicate that the electronic service quality of the JMO application still requires improvement. This study aims to analyze the effect of the e-service quality of the Jamsostek Mobile (JMO) application on the satisfaction of Old Age Security (JHT) beneficiaries at the BPJS Ketenagakerjaan Bukittinggi Branch Office. This study employed a quantitative approach with an associative research design. The e-service quality variable was measured using the E-S-QUAL model developed by Parasuraman, Zeithaml, and Malhotra (2005), while user satisfaction was measured using the End-User Computing Satisfaction (EUCS) model developed by Doll and Torkzadeh (1988). Data were collected through questionnaires distributed to respondents selected using an accidental sampling technique and analyzed using simple linear regression with SPSS version 21. The results indicate that e-service quality has a positive and significant effect on the satisfaction of JHT beneficiaries, as evidenced by a significance value of 0.000 (<0.05) and a calculated t value of 14.832, which is higher than the t table value of 1.98525. The coefficient of determination shows that e-service quality explains 69.8% of the variance in user satisfaction, while the remaining 30.2% is influenced by other factors beyond the scope of this study. These findings confirm that improving electronic service quality, particularly in terms of efficiency, fulfillment, system availability, and privacy, plays an important role in enhancing user satisfaction with the Jamsostek Mobile (JMO) application as a digital service platform of BPJS Ketenagakerjaan.